Genomic-based genotype and drug susceptibility profile of Mycobacterium kansasii in China - Wang, Yiting; Ou, Xichao; Zhao, Bing; Xia, Hui; Zheng, Yang; Zhou, Yang; Xing, Ruida; Song, Yuanyuan; Wang, Shengfen; Zhao, Yanlin; Zheng, Huiwen (Frontiers in Microbiology, 2025)
To analyze subtypes, microbiological characteristics and antimicrobial susceptibility of Mycobacterium kansasii in China, a total of 153 M. kansasii isolates, collected from national drug resistance surveillance, were genotyped with whole genome sequencing and explored the antimicrobial susceptibility with broth microdilution. All isolates were classified as M. kansasii type I based on Average Nucleotide Identity(ANI). The 153 M. kansasii representatives were differentiated into 3 clusters with 141 genotypes, including 17 isolates from a cluster and 136 isolates with unique patterns. The EXS-1, EXS-3 and EXS-5 regions were involved in all isolates. Rifabutin and clarithromycin were the most highly active against M. kansasii strains, with the susceptible rate of 100 and 99.35%, respectively. Followed by amikacin and linezolid, the resistance rate was 5.88 and 7.19%, respectively. The resistance rate to rifampin (RIF) was 22.22%. As for the antibiotics without the breakpoint values, all isolates had very low MIC50 (0.03 μg/mL) and MIC90 (≤0.06 μg/mL) values against bedaquiline, sutezolid, delamanid, and clofazimine. Except for ciprofloxacin and moxifloxacin, the resistance rate of other drugs in cluster 3 was higher than that in cluster 1 and cluster 2. In conclusion, M. kansasii type I was the predominant genotype in China, and rifabutin and clarithromycin presented strong activities. The new drugs, used for the treatment of multidrug - resistant tuberculosis, have the potential to be potent agents in the treatment of M. kansasii infection. The clustering might contribute to the high resistance rate of M. kansasii.